2018
DOI: 10.18203/2394-6040.ijcmph20180780
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity profile of communicable diseases in a tertiary care hospital of Chandrapur, Maharashtra

Abstract: Background: Worldwide, developed and developing countries are facing the double burden of communicable and non-communicable diseases. However, developing countries like India is more exposed and vulnerable due to multitude of factors. Objectives were to study the morbidity patterns of communicable diseases of indoor patients at tertiary care hospital and find out the seasonal distribution of the communicable diseases.Methods: A retrospective study was done over a period of 1 year from April 2016 to March 2017.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In contrast to our study, Dhoble et al study in Maharashtra and Datta et al study in Tripura showed female predominance while Kalyani et al study in Hyderabad showed no gender bias. [10][11][12] Thane district being an industrial area, there are many people who come to Thane for a good job. As a result, more males get admitted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study, Dhoble et al study in Maharashtra and Datta et al study in Tripura showed female predominance while Kalyani et al study in Hyderabad showed no gender bias. [10][11][12] Thane district being an industrial area, there are many people who come to Thane for a good job. As a result, more males get admitted.…”
Section: Discussionmentioning
confidence: 99%
“…In 10,13 Usually trends of admissions increase in monsoon and post monsoon season. But it was seen that it was decreased in 2020.…”
Section: Discussionmentioning
confidence: 99%